Modeling analysis on the cooling efficiency of composite phase change material-heat pipe coupling system in battery pack. (August 2022) - Tang, Ziyi; Feng, Renlang; Huang, Peifeng; Bai, Zhonghao; Wang, Qingsong
Abstract: Phase change material (PCM) cooling has attracted great attention in battery thermal management applications due to its compact structure and large latent heat of phase change. This study constructs a thermal management system consisting of the paraffin/copper foam metal composite phase change material and heat pipe. The accuracy of the simulation model is verified by comparing the experimental data. Numerical simulations are performed on the operating voltage and temperature of lithium-ion battery packs under different charging rates and ambient temperatures. The results show that copper foam-paraffin composite phase change material has the advantage of high thermal conductivity. The heat pipe can disperse heat in time to ensure the temperature uniformity of the module. Compared with different thermal management systems, the study found that the system can control the module temperature rise and temperature difference at 5 °C and 0.7 °C when charging at 1C in a high-temperature environment. The cooling efficiency of the composite PCM-heat pipe coupling system is more efficient than that of natural cooling and composite PCM cooling. Through simulation verification, the system can meet the working requirements of modules under different environments and different charging rates. However, under the dual conditions of high temperature and high rate, refrigeration or liquid cooling coupling should be considered to assist management in the future. In addition, this paper studies the influence of the size change of center distance between cells on system performance. It is believed that reducing the Y space appropriately is beneficial to saving cost and improving energy density, but excessively reducing the X space will make the module temperature rise and temperature difference change greatly. To meet the dual requirements of material utilization rate and temperature control management, a more suitable size range is given. Highlights: A simulation model of battery pack thermal management system with a new structure was established. The thermal contact resistance of different surfaces was considered to improve the simulation accuracy. Compared with other conventional cooling methods, the system has excellent performance in cooling efficiency and uniformity. The effects of charging rate, ambient temperature and structure size on system performance were analyzed.